First record of the genus Notiomys Thomas 1890 (Rodentia, Cricetidae) for Chile - Dâ€™Elía, Guillermo; Barria, Roderich; Teta, Pablo (THERYA, 2016)
The Patagonian assemblage of small mammals has long fascinated naturalists. Even when it is moderately diverse, several of its components are endemic to the region. One of these is the monotypic genus Notiomys, whose single species N. edwardsii is widely distributed in the steppes of Argentinean Patagonia. A dead mouse found in Parque Nacional Torres del Paine, Última Esperanza, Chile, which was determined as belonging to the species N. edwardsii. The just mentioned finding allows us to report the genus Notiomys for the first time to Chile. This result highlights the need of keeping doing field prospections even in areas whose mammal assemblages are presumably well characterized.